Повышение износостойкости защитных покрытий запорной арматуры для АЭС и магистрального трубопроводного транспорта - Kovaliok N. S. (Relevant lines of scientific research: theory and practice, 2016)
discussed technical solutions to improve the wear resistance of coatings of valves for nuclear power plants, and trunk pipelines.
Keywords: износостойкость; protective coatings; защитные покрытия; valves; арматуры; wear resistance